The power of the ego and its relation to the psychological pressures of players clubs Baghdad excellent degree of handball - mataab, Fouad (Journal of Physical Education, 2010)
The research includes the introduction and the value of the study. It investigates that Handball is one of the team games which is characterized by the effect of the players performance through the competition by many psychological variables, such as ego strength and stresses. The aims were identifying the ego strength and the stresses on the players, and identifying the relation between them, while the hypothesis was that a significant relation between the ego strength and the stresses. The researcher follows a descriptive style in investigating super Handball, and got that is a significant relation between the players, ego strength and the stresses, and the researcher recommends that is necessary to increase the coaches' interesting in players, psychological guidance and help them to solve there problems.